A Systematic Review of Ethical Leadership as a Panacea for Combating Sexual Harassment in Africa - Ijeoma Gloria Ukeni (Administrative Sciences, 2024)
Sexual harassment is an ongoing baseness that should be non-existent at work. Such immoral behaviours have psychological, physical, and behavioural impacts on victims, with no organisational benefit. Hence, it is imperative that positive actions against sexual harassment are needed, and leaders have a role to play. However, there are limited studies on how ethical leaders can contribute to the eradication process. This report, therefore, makes a compelling case for developing ethical leaders as champions against sexual harassment. It accentuates the positive effect of role-modelling ethical behaviours. Based on secondary data, traditional and systematic literature reviews were conducted on sexual harassment and ethical leadership in sub-Saharan Africa, respectively. The results of the thematic analysis showed that women are mostly the victims of sexual harassment due to the abuse of power and poor execution of harassment policies. The study offers laudable mechanisms such as the creation of an inclusive environment with zero tolerance for sexual harassment, the moral development of organisational members and the reorientation and support for victims. Given the ‘power distance’ culture of most African nations, the fight will be tough, but the benefits and prospects far outweigh the cost. Hence, recommendations and practical approaches to potential challenges are discussed.